ANALYSIS OF NURSING PRACTICE USING AN INNOVATIVE INTERVENTION INVOLVING THE ADMINISTRATION OF SLIMBER ICE TO ALLEVIATE THIRST IN PATIENTS WITH CHRONIC KIDNEY DISEASE (CKD) - Maulida Eka Cahyani; Thomas Ari Wibowo; Alfi Ari Fakhrur Rizal; Taharuddin Taharuddin (Cendekia Medika: Jurnal Stikes Al-Ma`arif Baturaja, 2026)
Chronic Kidney Disease (CKD) is a progressive and irreversible condition characterized by declining kidney function, which disrupts fluid balance and reduces patients’ quality of life. CKD patients undergoing hemodialysis often experience excessive thirst due to fluid intake restrictions, which can cause discomfort and increase the risk of treatment non-adherence. This study aims to analyze nursing practices involving the innovative intervention of administering slimber ice to reduce thirst in CKD patients in the Intensive Care Unit (ICU) at Iche Abdoel Moeis General Hospital in Samarinda. The method used was a case study with a descriptive approach involving one CKD patient undergoing hemodialysis. Thirst levels were measured using the Visual Analogue Scale (VAS) before and after the intervention. Slimber ice was administered for two consecutive days, with each session lasting 10 minutes and consisting of 6 ice cubes (5 ml per cube). The results showed that the thirst level before the intervention was in the moderate category (VAS 6 and 5), then decreased to the mild category (VAS 4 and 3) after the intervention, with an average decrease of 2 points. This intervention works by stimulating cold receptors and increasing oral cavity moisture, which helps reduce the perception of thirst. In conclusion, Slimber Ice is effective as a nonpharmacological therapy for reducing thirst, improving comfort, and supporting adherence to fluid restrictions in patients with chronic kidney disease.